(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
With the highlight of the automotive area in recent years, there was a need for more in-depth dynamic studies, as the demand for comfort and performance grew so, in this research UFVJM students by the Team Baja Espinhaço, explain how the suspension selection method for a Baja-type off-road vehicle does fabricate and the analyses carried out to ensure a better choice, considering how this can actuate on the prototype performance and showing how important is the learned theory in the classroom when applied to a project.